Perencanaan Pembangkit Listrik Tenaga Surya (PLTS) Atap Off Grid Di Mesjid Al-Anshar, Kelurahan Maliaro Ternate - Abbas, Muhammad yunus Hi; Rasyid, Ramly; Syaifuddin, Hafid (Patria Artha Technological Journal, 2025)
This solar power plant system illustrates a process of maximizing renewable energy utilization. Frequent power outages due to system disruptions cause damage to many electronic devices, so a system was designed to support electricity availability within the mosque. This research method utilizes qualitative research, systematically recording observations and interviews. The qualitative research process begins with establishing basic assumptions and the rules of thought that will be applied in the study. This study will utilize Helioscope software simulations, which simulate system operation to determine the arrangement and number of solar panels, batteries, and inverters used under specified conditions, as well as the system's operation. The results of the PLTS system simulation designed using Helioscope software include 4 units of Longi PLTS Modules, LRS-72HPH-550M (220) with a capacity of 550 W, 4 units with a total installed capacity of 2.20 kW, as well as 1 unit of SPF 5000 ES (5 kW) inverter and 3 units of Lithium iron Phosphate batteries (48 V, 100 Ah).